Media, Politics and Public Relations; Context of An Investigation: Trnc AND Turkey - CELIK, MUSTAFA UFUK; CELIK, SAIT; KASIMOGLU, SINEM (The journal of contemporary issues in business and government, 2021)
It is a well known incontrovertible fact that the media, which is defined because the biquadrate after the legislative, executive and judicial powers within the development of democracy, acts as a bridge between politics and society with all its traditional and new elements. The media, which has been interacting with politics since the primary moment of its emergence, is beyond being an influence that directs individuals in almost every area of life; It also plays a fundamental role in determining the political agenda and evaluating the political leaders. during this study, today's media, which has become an increasing force gradually effect, their impact on the connection between popular opinion and therefore the political establishment, which has similar social and cultural characteristics of Northern Cyprus Turkish Republic (TRNC) and Turkey society by examining especially, are evaluated. press screening publication and review of the literature conducted in Turkey, the media, said that their actions and news during a fairly wide audience of no simpler within the orientation of replacing or convictions. If a smaller scale within the TRNC with transmission power of the media that the overwhelming majority of publications for his or her own political opinion, compared to Turkey media about changing the orientation and convictions popular opinion are often expressed as less effective.